HUBUNGAN KEPADATAN TERIPANG (HOLOTHUROIDEA) DENGAN KERAPATAN LAMUN DI PERAIRAN PULAU BUNTAL-TELUK KOTANIA, KABUPATEN SERAM BAGIAN BARAT - Bachmid, Salahuddin; Siahainenia, Laura; Tupan, Charlotha I (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2020)
Buntal island has rich potency of both seagrass and sea cucumber. Seagrass ecosystem is the habitat of one among the economic valued biota, sea cucumber. The purpose of the research are: 1) to know the environmental condition; 2) to know the seagrass condition; 3) to know the community structure of the sea cucumber; 4) to know the spatial distribution of sea cucumber in the seagrass ecosystem; and 5) to analyze the relation of the density of sea cucumber and the density of seagrass in the waters of Buntal island-Kotania Bay, West Seram Regency. The sample are taken systematically using Belt Transect. The research is located in 2 observation stations where each station is determines into 3 zones. Seagrass condition is analyzed consist of density, frequency of presence and percentage of seagrass cover. The community structure of sea cucumber includes the density and frequency of presence. Spatial distribution mapping on the sea grass ecosystem is using ArcGIS application. The simple linear regression analysis and Pearson correlation are used to analyze the relation between the density of the sea cucumber and the density of the seagrass. The result of the research shows that the whole environmental parameters on the waters of Buntal Island support the existence of both the seagrass and the sea cucumber. The research finds 5 varieties of seagrass and 11 varieties of sea cucumber. Thalassia hemprichii is the seagrass variety that dominates the ecosystem while Holothuria leucospilota and H. atra are the varieties of sea cucumber with high density on Buntal Island waters. The healthy seagrass condition (well covered) is found in station 1 and bad health condition (worse covered) is found in station 2. The relation between the density of sea cucumber and the density of seagrass on the waters of Buntal Island, it is concludes that there is a high relation where the higher the density of seagrass the higher the density of the sea cucumber. ABSTRAK Pulau buntal memiliki potensi sumberdaya lamun maupun teripang yang melimpah. Ekosistem lamun sebagai habitat bagi sumberdaya teripang yang merupakan salah satu biota berekonomis penting. Tujuan dari penelitian ini adalah: 1) mengetahui kondisi lingkungan; 2) mengetahui kondisi lamun; 3) mengetahui struktur komunitas teripang; 4) mengetahui distribusi spasial teripang pada ekosistem lamun; 5) menganalisis hubungan kepadatan teripang dengan kerapatan lamun di perairan Pulau Buntal-Teluk Kotania, Kabupaten Seram Bagian Barat. Pengambilan sampel lamun dan teripang dilakukan secara sistematik menggunakan metode Belt Transek. Lokasi penelitian terdiri dari 2 stasiun pengamatan dan setiap stasiun terbagi menjadi 3 zona. Kondisi lamun yang dianalisis meliputi kerapatan, frekuensi kehadiran dan persentase tutupan lamun. Struktur komunitas teripang meliputi kepadatan dan frekuensi kehadiran. Peta distribusi spasial teripang pada ekosistem lamun menggunakan aplikasi ArcGIS. Analisis regresi linear sederhana dan korelasi pearson untuk melihat pengaruh serta hubungan kepadatan teripang dengan kerapatan lamun. Berdasarkan hasil penelitian menunjukan bahwa sacara keseluruhan parameter lingkungan di perairan Pulau Buntal sangat mendukung untuk kehidupan sumberdaya lamun maupun teripang. Ditemukannya lima jenis lamun dan 11 jenis teripang. Thalassia hemprichii merupakan jenis lamun yang sangat mendominasi pada komunitas lamun di perairan Pulau buntal. Jenis teripang Holothuria leucospilota dan H. atra memiliki nilai kepadatan yang tinggi pada perairan pulau Buntal. Dengan kondisi lamun sehat (tutupan baik) pada stasiun 1 dan tidak sehat (tutupan rusak) pada stasiun 2. Hubungan kepadatan teripang dengan kerapatan lamun pada Perairan Pulau Buntal dapat disimpulkan terdapat hubungan yang tinggi sehingga semakin tinggi kerapatan lamun akan diikuti oleh tingginya kepadatan teripang. Kata Kunci: Lamun, teripang, kepadatan, ekosistem lamun, Pulau Buntal